Memories of Poland [bladmuziek] : a collection of its best-loved melodies with English and the original Polish text - Stojowski, Sigismond; Paul, Olga (London New York : M.I. Kolin Edward B. Marks)
Bibliotheek Camille Huysmans
Pools
Engels
Partituur
Keywords: klassieke liederen; volksliederen; Polen